Bioprospecting in nicaragua: advances in search of agricultural, industrial and environmental applications - Páramo-Aguilera, L.A.; Fonseca-Cruz, E.J.; Delgado-Silva, H.D.; Cabistán-calderón, K.E.; Ríos-Guevara, C.K. (Nexo Revista Científica, 2018)
Nicaragua belongs to one of the mega diversity blocs of the world. Since it is considering to be a geographic bridge, it possesses a privileged tropical position that translates into more than 20 different rich ecosystems in biodiversity. Due to bio-prospecting we understand the research in order to identify species, variety, genes and products with potential or actuals current uses for the human beings. The bio-prospecting advances reported in this article, has permitted until to date, to obtain 92 isolated forms in the Pedro Lazo cheese handcrafted company (76 bacterial, 3 yeast fungus type and 13 isolate filamentous fungus type). A total of 68 isolate in the handcrafted mine from la Libertad, Chontales (44 isolated bacterial, 6 yeast fungus type and 18 isolated filamentous funguses type). From the ecological reserve, El Chocoyero / El Brujo, 44 pure isolated were obtained (22 bacterial and 22 filamentous fungus). Finally; from Rio Chiquito in Leon city, 51 pure isolated were obtained (43 isolated bacterial, 7 filamentous fungi and 1 yeast fungi type). In summary: 255 isolate were obtained between bacterial, filamentous fungus and fungi yeast type, in which we expect to find many isolated with enormous biotechnological potentials.